Outcome of localized liver‐bile duct rhabdomyosarcoma according to local therapy: A report from the European Paediatric Soft‐Tissue Sarcoma Study Group (EpSSG)‐RMS 2005 study. Issue 7 (28th March 2019) - Guérin, Florent; Rogers, Timothy; Minard‐Colin, Véronique; Gaze, Mark N.; Terwisscha, Sheila; Van Noesel, Max; De Corti, Federica; Guillén Burrieza, Gabriela; De Salvo, Gian Luca; Kelsey, Anna; Orbach, Daniel; Ferrari, Andrea; et al.
Abstract: Objectives: To evaluate the impact of local therapies on the outcome of patients with liver‐bile duct rhabdomyosarcoma (LBDRMS). Methods: Data of 30 patients included in the EpSSG‐RMS 2005 study were analyzed. Results: The median age at diagnosis was 3 years (11 months–8 years). All patients had non‐alveolar histology. Fifteen patients had a tumor > 5 cm and six had enlarged regional lymph nodes on imaging. Eight patients (27%) had primary surgery (1 R0). Six of them received external beam radiotherapy (EBRT). All are in first complete remission (CR1) except one (R1, EBRT +, local relapse, death). Six patients (20%) received EBRT without surgery: one had local relapse and died. Sixteen patients (53%) underwent delayed surgery, with 12 achieving R0 margins, which were higher than those in the primary surgery group ( P = 0.003). Three patients with R0 margins received EBRT; one had a metastatic relapse and died. Nine patients with R0 resection did not receive EBRT, three relapsed locally (two deaths). Four R1 patients received additional EBRT without relapses. Local relapse occurred in two among 19 patients with EBRT and three among 11 without EBRT ( P = 0.326). At a median follow‐up of 61 months (48–84 months), five patients died; all had a tumor size > 5 cm ( P = 0.01). The five‐year overall survival was 85% (95% CI, 65–94), and event‐free survival was 76% (95% CI, 54–89). Conclusion: This analysis did not show any significant difference in outcome between irradiated and nonirradiated patients. Local relapse in LBDRMS is related to initial tumor size and is often fatal.